Guilt Focused Intervention for Family Caregivers. Preliminary Results of a Randomized Clinical Trial. Issue 5 (20th October 2022) - Romero-Moreno, Rosa; Márquez-González, María; Gallego-Alberto, Laura; Cabrera, Isabel; Vara-García, Carlos; Pedroso-Chaparro, María Del Sequeros; Barrera-Caballero, Samara; Losada, Andrés
ABSTRACT: Objectives: A pilot randomized controlled trial study was conducted for testing the efficacy of a novel Guilt Focused Intervention (GFI), that was compared with a Cognitive Behavioral Intervention (CBI) for caregivers of people with dementia with high levels of guilt and distress. Methods: Participants were 42 caregivers who were randomized assigned to the intervention conditions. Results: Participants in the GFI showed significant reductions in depression, anxiety, and guilt at posttreatment and follow-up. Participants in the CBI presented reductions in anxiety and guilt at posttreatment and follow-up. Clinically significant change for guilt was found in 62.5% in the GFI and 9.09% in the CBI group at posttreatment. At follow-up, 58.33% in GFI and 12.5% in the CBI group were recovered. Conclusions: The preliminary results of this pilot study suggest that caregivers with significant levels of guilt and distress might benefit from an intervention specifically designed to target guilt feelings. Clinical Implications: A novel and initial intervention approach specifically designed for targeting caregivers' feelings of guilt might have the potential to reduce caregiver's emotional distress.